TRACER STUDY SARJANA (S1) TERAPAN KEUANGAN FEB UNIVERSITAS TRISAKTI - Curry, Khirstina (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
This study aims to analyze how the tracer study of the Bachelor of Applied Finance. The purpose of this study is to obtain accurate informationabout applied undergraduate graduates both in terms of suitability of the field of work with education, suitability of the knowledge obtained with thejob and the process of job waiting time. This information is very important because from there an overview of important things that are input inimproving the quality of graduates and science and skills. The suitability of knowledge and skills in accordance with DUDIKA is the main focus ofthe need for this research. It is hoped that the results of this research will produce a curriculum that is adaptive (according to market needs) and inaccordance with the field of profession and the scope of association. To obtain this information, a qualitative method was used by distributingquestionnaires to alumni who graduated in 2015 to 2020. The result was only 61 percent of the total population for 5 years. This shows that the roleof the study program is still necessary in increasing the motivation and attachment of alumni to be willing to give their response to their almamater.